Hunting for Employees, Employers, Independent Contractors, Dependent Contractors and Other Figments of the Legal Imagination - Langille, Brian; Mayer-Goodman, Ben (Dalhousie Law Journal, 2025)
This paper exposes the falsity of a fundamental assumption of labour law—namely that there is such a thing as an “employee” or “employer” or “independent contractor” and that such legal entities can be “found” through an examination of the facts. As we shall demonstrate, once we have discarded the flawed assumption that “employees” or “employers” (or “independent” or “dependent contractors,” or “worker,” or any other legal creature) exist in the real world, we see that labour law’s purpose as it is currently widely understood is also fundamentally flawed. It is from this standpoint that a new conceptual framework for—and normative underpinning of—labour law emerges.